Supernumerary Nostril: Two Years Follow-Up. Issue 4 (June 2017) - Labib, Amir; Elshahat, Ahmed
Abstract : Abstract: Supernumerary nostril is a very rare congenital anomaly of the nose. Since the first patient reported by Lindsay in 1906, few number of patients were reported in the literature. Various types had been described with different surgical modalities for correction. It can be isolated or associated with other malformations such as facial cleft, esophageal atresia, and imperforate anus. Most of the patients are unilateral, but it may be bilateral. It may have a communication with a normal nasal cavity or not. In this study, the authors present a case of a 1-year-old male with a positive perinatal history of teratogen exposure had isolated supernumerary left nostril with communication to the nasal cavity. The authors will discuss different theories related to supernumerary nostril development, differences between published reports, the proposed surgical techniques, and the outcome of their treatment approach.